Spatial weights in loudness judgements - Hots Jan; Oberfeld Daniel; Verhey Jesko L. (Acta Acustica, 2024)
In everyday life, the auditory system often receives input from various sound sources at different positions in space more or less simultaneously. The present study investigates how listeners weight different spatial positions when judging the overall loudness of a spatially distributed sound field. Spatial weights were measured in two conditions. In both conditions, sounds were presented from five spatial positions: front, left, right, top and back, using five loudspeakers distributed spatially around the listener. In the first condition, bandpass noises were presented simultaneously on all five loudspeakers. The sounds emanating from the different loudspeakers did not overlap spectrally, to ensure that they could be differentiated from each other. In the second condition, a broadband noise was presented at each of the five spatial positions. In this condition, sounds from the five different positions were presented consecutively. In both conditions, listeners judged the overall loudness of the sound fields. Before measuring spatial weights, all sounds were equalised in loudness. Both conditions showed virtually identical spatial weights for all five spatial positions. Thus, the weight assigned to a specific sound source in judgments of the overall loudness of spatially distributed sound fields appears to be unaffected by the spatial position of the source.